2021
DOI: 10.2355/isijinternational.isijint-2020-367
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Simulation on the Effect of Gas Pressure on the Formation of Local Dry Underwater Welds

Abstract: The obvious feature of local dry underwater welding is the local drainage of the welding area. The choice of drainage method is one of the important factors affecting the quality of underwater welds. Based on hydrodynamics and thermodynamics, the internal gas flow characteristics and arc combustion of the micro-drainage cover with dual-gas curtains is used to simulate which could not be directly observed in the micro-drainage cover with FLUENT, and then the influence of micro-drainage cover on the weld formati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…14) Xu found the magnitude of surface tension has a strong influence on the rising of bubbles in the liquid phase. 15) For high nitrogen steel, pressurized metallurgy is recognized as one of the most effective methods for manufacture, including pressurized induction melting, pressurized electroslag remelting (PESR), et al [16][17][18][19] Pressure is a critical metallurgical parameter that has been shown to considerably enhance nitrogen solubility and impede the formation of nitrogen pores. 1,[20][21][22] Despite the extensive research on the formation process of nitrogen bubbles in high nitrogen steel ingots, the impact of solidification pressure on the rising and breakup of nitrogen bubbles in high nitrogen molten steel is still not well comprehended.…”
Section: Introductionmentioning
confidence: 99%
“…14) Xu found the magnitude of surface tension has a strong influence on the rising of bubbles in the liquid phase. 15) For high nitrogen steel, pressurized metallurgy is recognized as one of the most effective methods for manufacture, including pressurized induction melting, pressurized electroslag remelting (PESR), et al [16][17][18][19] Pressure is a critical metallurgical parameter that has been shown to considerably enhance nitrogen solubility and impede the formation of nitrogen pores. 1,[20][21][22] Despite the extensive research on the formation process of nitrogen bubbles in high nitrogen steel ingots, the impact of solidification pressure on the rising and breakup of nitrogen bubbles in high nitrogen molten steel is still not well comprehended.…”
Section: Introductionmentioning
confidence: 99%